Mentzer Index and Red Cell Distribution Width Index in differentiating iron deficiency anemia and β-thalassemia trait - Rabab H. Elshaikh; Ashok Kumar Sah; Abdelrahman Mohamed Abukanna; Abdulrahman Algarni; Ammar Abdelmola; Hussam Ali Osma; Tagwa Yousif Elsayed Yousif; Elryah I. Ali; Hiba Ali; Ayman Hussein Alfeel (Italian Journal of Medicine)
The differentiation between iron deficiency anemia (IDA) and β-thalassemia trait (βTT) is essential for managing microcytic hypochromic anemia. Indices such as the Mentzer Index (MI) and Red Cell Distribution Width Index (RDWI) serve as cost-effective preliminary diagnostic tools. This study evaluates the reliability and diagnostic accuracy of these indices. This cross-sectional study included 200 patients with microcytic hypochromic anemia at Khartoum public hospitals in 2021. MI was calculated as mean corpuscular volume (MCV)/red blood cell (RBC) count and RDWI as (MCV×RDW)/RBC. Sensitivity, specificity, and the Youden Index were determined. Results revealed that among 200 patients, 100 had IDA, and 100 had βTT. Both groups showed microcytic hypochromic features, though RBC was slightly elevated in βTT. IDA patients had decreased serum iron, while hemoglobin (Hb) electrophoresis revealed increased HbA2 and HbF in βTT. MI showed a sensitivity of 90% (βTT) and 95% (IDA), with a specificity of 95% and 90%, respectively. RDWI had a sensitivity of 83% (βTT) and 96% (IDA), with a specificity of 96% and 83%. MI had a higher Youden Index (0.85 for βTT). In conclusion, both indices effectively differentiate IDA and βTT, but MI is the most reliable and cost-effective tool.